Credit market development and firm innovation: Evidence from the People's Republic of China - Hua Shang; Quanyun Song; Yu Wu (Asian Development Bank Institute (ADBI), 2017)
From the perspective of credit allocation, this paper analyzes the effects of credit market development on the innovative capacities of industrial firms in the People's Republic of China. Using a large dataset of industrial firms in 31 provinces in the People's Republic of China, we find that credit market development enhances firms' product innovation incentives and outcomes. We further show that firms' credit constraints and firms' performances are two channels through which credit market development affects innovative capacities of firms. Our results are neither driven by the increase in the quantity of credit, nor by the increase in the number of firms in a province. The results are robust to different samples, different estimation methods, and alternative measures of credit market development.
Keywords: G15; O31; R11; 330; Economics; Finance sector development; Industry and trade; China; People's Republic of